Ascertaining transparency and accountability in the practice of assessment of claims for loss and damage in contractor's all risks (car) takaful - Mohd Fauzi, Puteri Nur Farah Naadia; Abdul Rashid, Khairuddin; Ahmad Sarkawi, Azila; Aripin, Srazali; Hasan, Sharina Farihah (Sultan Agung Islamic University (UNISSULA), 2015)
In construction contracts, it is a pre-requisite for Contractors to secure insurances to cover construction works related risks. Due to the interest and demand to apply Shariah compliance products in business transactions, with the advent of takaful and its products that cover areas including risks in construction works, it is observed that more Contractors are using Contractor’s All Risks (CAR) Takaful certificates in lieu of the conventional CAR policies. However, the lack of transparency and accountability on the way in which claims for construction works loss and damage were assessed have led to critiques and concerns raised on such issues on CAR Takaful. Consequently, a study with the aim to ascertain transparency and accountability in the practice of assessment of claims for loss and damage under CAR Takaful was conducted via critical review of literature and discussions with the experts of construction, Shariah and insurance/takaful fields. The key results from the study suggest that issues on the lack of transparency and accountability in assessing construction works loss and damage for compensation were relatively genuine. In fact, it appears to be the case that assessment for compensation relies almost entirely on customary practices and internal experts’ decisions. The study concluded with recommendations to enhance transparency and accountability in the assessment of claims in CAR Takaful certificates.